2012
DOI: 10.3892/mmr.2015.3396
|View full text |Cite
|
Sign up to set email alerts
|

Protective mechanism of Korean Red Ginseng in cisplatin-induced ototoxicity through attenuation of nuclear factor-κB and caspase-1 activation

Abstract: Cisplatin is an effective anti-cancer drug; however, one of its side effects is irreversible sensorineural hearing damage. Korean Red Ginseng (KRG) has been used clinically for the treatment of various diseases; however, the underlying mechanism of KRG treatment of ototoxicity has not been studied extensively. The present study aimed to further investigate the mechanism of KRG on cisplatin-induced toxicity in auditory HEI-OC1 cells in vitro, as well as in vivo. The pharmacological effects of KRG on cisplatin-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 54 publications
1
11
0
1
Order By: Relevance
“…This model did not cause any endometrial hyperplasia; however, any change in uterine weights and the histopathology of the uterus, significant ovarian weight gain, ovarian hyperplasia, and the formation of numerous cysts were the main symptoms of PCOS in this study, which was in accordance to previous animal evidence [1,14] as shown in Fig. 2A.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This model did not cause any endometrial hyperplasia; however, any change in uterine weights and the histopathology of the uterus, significant ovarian weight gain, ovarian hyperplasia, and the formation of numerous cysts were the main symptoms of PCOS in this study, which was in accordance to previous animal evidence [1,14] as shown in Fig. 2A.…”
Section: Discussionsupporting
confidence: 92%
“…In this context, many limitations exist with regard to the prevention, protection, or definite treatment of PCOS, thus increasing the public's concerns toward alternative medications. Korean red ginseng is one of the most popular herbal remedies in other disease models and is known to have certain anti-inflammatory [13] and antioxidant effects [14] through activation of the NF-κB pathway [15]. However, the estrogenic effects of Korean red ginseng extract (KRGE) is still conflicting based on in vitro, in vivo [16] and clinical evaluations of sexual disorders [17].…”
Section: Ovarian Cysts Disappear After 14-day Oral Regimen Of Korean mentioning
confidence: 99%
“…186 In several animal models, ginseng protected animals from cisplatin nephrotoxicity and ototoxicity. [187][188][189][190][191][192] Ginseng in rats reduced cisplatininduced nausea and weight loss. 193,194 632…”
Section: Cancermentioning
confidence: 98%
“…KRG extracts, or its specific saponins, were shown to have antiapoptotic and antioxidant properties in various tissues both in vitro and in vivo [8] . Recently, it was shown that KRG has otoprotective properties against gentamicin [9,10] , 3-nitropropionic acid [12] , and CDDP-induced ototoxicity [8,13] . These studies revealed that KRG mainly works by inhibition of some proapoptotic genes such as caspase-1, caspase-3, and the TNF family of genes and by enhancement of antiapoptotic gene expression such as bcl-2 [8][9][10][11][12][13] .…”
Section: Discussionmentioning
confidence: 99%
“…KRG has been found to be effective in various problems that cause hearing loss such as gentamycin ototoxicity, age-related hearing loss, or 3-nitropropionic acid-induced cochlear damage [8][9][10][11][12] . CDDP-induced hearing loss has been studied in one in vitro and in one in vivo study [8,13] . The aim of this study was to evaluate the effects of different doses of KRG on CDDP ototoxicity both in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%